Second-order decoherence mechanisms of a transmon qubit probed with thermal microwave states. (7th April 2017) - Goetz, J; Deppe, F; Eder, P; Fischer, M; Müting, M; Martínez, J Puertas; Pogorzalek, S; Wulschner, F; Xie, E; Fedorov, K G; Marx, A; Gross, R
Abstract: Thermal microwave states are omnipresent noise sources in superconducting quantum circuits covering all relevant frequency regimes. We use them as a probe to identify three second-order decoherence mechanisms of a superconducting transmon qubit. First, we quantify the efficiency of a resonator filter in the dispersive Jaynes–Cummings regime and find evidence for parasitic loss channels. Second, we probe second-order noise in the low-frequency regime and demonstrate the expected T 3 temperature dependence of the qubit dephasing rate. Finally, we show that qubit parameter fluctuations due to two-level states are enhanced under the influence of thermal microwave states. In particular, we experimentally confirm the T 2 -dependence of the fluctuation spectrum expected for noninteracting two-level states.